Nakládání s PET odpadem v rámci českého odpadového hospodářství - Hanáček, Ondřej (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2023)
Předmětem této práce je popis systémů sběru a nakládání s PET odpadem v rámci českého odpadového hospodářství. Podstatnou část práce tvoří popis uvažovaného zálohového systému na nápojové PET lahve. Součástí je porovnání těchto systémů společně s analýzou dopadů, které by případné zavedení zálohového systému mělo na obce, zpracovatele odpadu, prodejce a výrobce. Ekonomické nároky na provoz obou systémů jsou porovnány na konkrétním regionu ČR, za tímto účelem byl navržen přístup k posouzení provozních nároků a byl sestaven výpočtový nástroj v MS Excel.

The subject of this thesis is a description of PET waste collection and management systems within the Czech waste management. The essential part of this thesis is a description of the considered deposit-refund system for PET beverage bottles. It includes a comparison of these systems together with an analysis of the impacts that the possible introduction of a deposit-refund system would have on municipalities, waste processors, retailers, and producers. The economic requirements for the operation of both systems are compared on a specific region of the Czech Republic, for this purpose an approach to the assessment of operational requirements was designed and a calculation tool in MS Excel was compiled.
PET waste treatment in the Czech waste management
Keywords: Komunální odpad; PET odpad; zálohový systém; cirkulární ekonomika; Municipal waste; PET waste; deposit-refund system; circular economy